A MORPHOLOGICAL ANALYSIS ON AFFIXES IN TOMBULU LANGUAGE - Randy Kristoforus Senduk; Sanerita T. Olii; Sarah Kamagi (Journal of English Culture, Language, Literature and Education, 2021)
This study aimed to reveal affixes' form and meaning in Tombulu language tenses, especially on past, present, and future tenses. Descriptive qualitative method used with applying Arikunto's procedure of collecting data which were interview and documentation. While, in analyzing data used Miles & Huberman which consisted of data reduction, data display, and conclusion drawing. This study showed that there were different functions of Affixes in the tenses of Tombulu language and English. The simple past tense was Infix -im- and -in-, which were placed after vocal or consonant phonemes. Simple present tense with Prefix mah- which was located to the beginning of the word. Simple future tense with Infix -um-, which was placed after vocal or consonant phonemes. Especially for the Infix -um- and -im-, if it was combined with a root word that begins with the consonant phonemes /p/ and /w/, then there was a change where the Infix -um- à (u)m and the infix -im- à nim. Affixes in Tombulu language tenses had different functions of affixes in English.